Revisiting Us,ak Terakki-i Ziraat Turkish Joint Stock Company (1925-1931): A Case Study of Turkey's Early Financial Reporting Culture - Guvemli, Batuhan; Aslan, Muhsin (AMER ACCOUNTING ASSOC, 2023)
This research offers an in-depth examination of the early financial reporting culture in Republican Turkey, using the Us,ak Terakki-i Ziraat Turkish Joint Stock Company (Us,ak Sugar Company) as a case study. The analysis of the company's financial statements from 1925 and 1931 reveals the development of financial reporting practices during a transformative period, marked by industrialization efforts and the introduction of the 1926 Turkish Commercial Code and Income Tax Law. The study identifies both progress and challenges in financial reporting, including detailed fixed assets classifications, accounting irregularities, inadequate auditing and working capital management practices. The findings indicate that these issues, alongside macroeconomic factors, have contributed to the company's liquidation in 1932. This failure could have indirectly catalyzed a shift toward statist economic policies in the 1930s.
Keywords: accounting history; Us , ak Sugar Company; surviving business records; financial reporting.; INDUSTRIALIZATION; Business & Economics